Peranan Kegiatan Patroli Keamanan Sekolah Terhadap Upaya Membangun Rasa Tanggung Jawab dan Sikap Disiplin Peserta Didik - Nabila Nabila; Hermi Yanzi; Yunisca Nurmalisa (Jurnal Kultur Demokrasi, 2018)
This study arms to determine the role of school security patrol activities on the effort to build of a sense of responsibility and discipline attitude of students in the state junior high school country 23 bandar lampung school year 2017/2018. The method used in the research using descriptive method with quantitative approach. The population in this study were 7th grade students In Junor High School Country 23 Bandar Lampung numbering 31 people. Based on testing and data analysis that there is a role for school security patrol activities towards effort to build of sense of responsibility and disciplinary attitude of students in junor high school 23 bandar lampung2017/2018 year.with the acquistion and analysis result of the relationship by using the formula Chi Square, indicating that school security activities play a role in building a sense a sense of responsibility and disciplinary attitudes of student In Junior High School 23 Bandar Lampung.Penelitian ini bertujuan untuk mengetahui peranankegiatan patroli keamanan sekolah terhadap upaya membangun rasa tanggung jawab dan sikap disiplin peserta didik di SMPNegeri 23 Bandar Lampung Tahun Pelajaran 2017/2018.Metode yang di gunakan dalam penelitian ini menggunakan metode deskripsi dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah peserta didik kelas 7 di SMPN 23 Bandar Lampung yang berjumlah 31 orang. Berdasarkan pengujian dan analisis data bahwa terdapat peranan kegiatan PKS terhadap upaya membangun rasa tanggung jawab dan sikap disiplin peserta didik di SMP Negeri 23 Bandar Lampung Tahun Pelajaran 2017/2018. Dengan perolehan dan hasil analisis uji keeratan hubungan dengan menggunakan rumus Chi Kuadrat, menunjukkan bahwa kegiatan PKS berperan dalam membangun rasa tanggung jawab dan sikap disiplin peserta didik di SMPN 23 Bandar Lampung.Kata kunci: disiplin, pks, tanggung jawab